Secondary radiation measurements for particle therapy applications: prompt photons produced by 4He, 12C and 16O ion beams in a PMMA target. (23rd January 2017) - Mattei, I; Bini, F; Collamati, F; De Lucia, E; Frallicciardi, P M; Iarocci, E; Mancini-Terracciano, C; Marafini, M; Muraro, S; Paramatti, R; Patera, V; Piersanti, L; et al.
Abstract: Charged particle beams are used in particle therapy (PT) to treat oncological patients due to their selective dose deposition in tissues with respect to the photons and electrons used in conventional radiotherapy. Heavy ( Z   >  1) PT beams can additionally be exploited for their high biological effectiveness in killing cancer cells. Nowadays, protons and carbon ions are used in PT clinical routines. Recently, interest in the potential application of helium and oxygen beams has been growing. With respect to protons, such beams are characterized by their reduced multiple scattering inside the body, increased linear energy transfer, relative biological effectiveness and oxygen enhancement ratio. The precision of PT demands online dose monitoring techniques, crucial to improving the quality assurance of any treatment: possible patient mis-positioning and biological tissue changes with respect to the planning CT scan could negatively affect the outcome of the therapy. The beam range confined in the irradiated target can be monitored thanks to the neutral or charged secondary radiation emitted by the interactions of hadron beams with matter. Among these secondary products, prompt photons are produced by nuclear de-excitation processes, and at present, different dose monitoring and beam range verification techniques based on prompt- γ detection are being proposed. It is hence of importance to perform γ yield measurement in therapeutic-like conditions. In this paper we report on the yields of prompt photons produced by the interaction of helium, carbon and oxygen ion beams with a poly-methyl methacrylate (PMMA) beam stopping target. The measurements were performed at the Heidelberg Ion-Beam Therapy Center (HIT) with beams of different energies. An LYSO scintillator, placed at 60 ° and 90 ° with respect to the beam direction, was used as the photon detector. The obtained γ yields for the carbon ion beams are compared with results from the literature, while no other results from helium and oxygen beams have been published yet. A discussion on the expected resolution of a slit camera detector is presented, demonstrating the feasibility of a prompt- γ -based monitoring technique for PT treatments using helium, carbon and oxygen ion beams.